Cortical reorganization following dorsal spinal injuries in newborn monkeys reveals a critical period in the development of the somatosensory cortex - Neeraj Jain; Hui-Xin Qi; Arun Raman; David Lyon; Jon H. Kaas (Proceedings of the National Academy of Sciences, 2025)
Lesions of the dorsal columns of the spinal cord in adult macaque monkeys lead to the loss of hand inputs and large-scale expansion of the face inputs in the hand region of the somatosensory cortex. Inputs from alternate spinal pathways do not reactivate the deafferented regions of area 3b. Here, we determined how transections of the dorsal columns done within a few days after birth affect the developing somatosensory cortex. Dorsal columns were transected between the 3rd and 12th postnatal day (PND), and the somatosensory cortex was mapped when the macaques were over 3 y old. There were two distinct outcomes depending on the age at the time of the lesion. In monkeys lesioned between the 3rd and 5th PND, neurons in the entire hand region of area 3b and the adjacent somatosensory cortex responded to touch on the hand. An alternate spinal pathway must have replaced the lost pathway. In monkeys lesioned between the 9th and 12th PND, neurons in the deafferented hand region did not respond to touch on the hand. There was medialward expansion of the face representation into the deafferented cortex and a lateral expansion of the arm representation as in lesioned adults. Thus, different mechanisms underlie the reorganization of area 3b and the adjacent somatosensory cortex following identical spinal cord injuries sustained as early or late newborns. The results suggest that alternate spinal cord pathways can develop within a critical period before the 9th PND, but not later.